Health Education based on 10 Steps at Mother Knowledge Level in Handling Febrile Seizure on Toddler - Ernawaty Siagian; Vera Manalu (Journal of Nursing Care, 2018)
Febrile seizure rate on toddler was quite high and tended to increase every year. This was because as toddler experiencing febrile seizures they were not properly handled by the parents. Febrile seizure in toddler if not treated quickly can affect the increasing in seizure frequency and can cause death. The capability of mother in handling febrile seizure must be based on the right knowledge of febrile seizure. The purpose of this study was to determine the level of knowledge of the mother before and after health education based on 10 steps in handling febrile seizure on toddler in Bandar Lampung Adventist Hospital. Experimental research method with one group pretest-posttest designed with random sampling technique approach involving 80 mothers with 0 to 5 year old who had fever being hospitalized. The researchers prepared 10 images of steps in handling febrile seizures randomly and asked the respondents to arrange the pictures according to their knowledge. The results were observed to determine their knowledge rearranging as pretest data. Afterward, health education was given about 10 correct steps. Thereafter, reobserved was made and the knowledge in arranging 10 images was obtained as post test data. The knowledge score before health education was 20.75% and after was 83.75%. While the analytical test used paired t test. The results showed a significant relationship between knowledge before and after health education. p value = 0.00 < 0.05. The results showed that the value of tcount (14.26) > t table (2.26). Increased knowledge in mothers reduced the risk of recurrence of febrile seizures in toddler and the nurse who had not tought these steps needed to run regularly to the mothers whose child was being hospitalized.